Pengaruh Pesta Adat Towani Tolotang Terhadap Peningkatan Pendapatan Pedagang Kaki Lima Di Kabupaten Sidenreng Rappang - Alif Afian Nasir Agustina Saini; Herman Dema; Abdul Jabbar; Sandi Lubis (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
The Towani Tolotang Traditional Ceremony, which is held annually in Tellu Limpoe District, Sidenreng Rappang Regency, not only serves as a cultural event but also acts as a driving force for the local economy. The presence of street vendors (PKL) during this cultural celebration creates significant economic opportunities. However, the lack of understanding of how the Towani Tolotang ceremony impacts the income of street vendors (PKL) in Tellu Limpoe District, Sidenreng Rappang Regency. This study aims to examine the effect of the Towani Tolotang traditional ceremony on the increase in PKL income. The method used is a quantitative approach with a survey technique through closed-ended questionnaires distributed to 35 PKL respondents. Data were analyzed using simple linear regression with the help of SPSS. The results show that the traditional ceremony has a positive and significant effect on increasing PKL income, with an average income increase of 82%. The regression analysis yielded an R² value of 0.166 and a significance of 0.015 (< 0.05), supporting the research hypothesis. The main factors driving the increase in income include high visitor enthusiasm (85%), strategic location, product types, duration of the event, as well as the active role of the traditional committee and support from the local government. This traditional ceremony has proven to strengthen the economic circulation of the informal sector while also strengthening social relationships and the cultural identity of the community. In the future, better collaboration between the local government and the traditional organizers has the potential to optimize the role of the traditional ceremony as part of a strategy for developing a culture-based economy.